Spinal Intradural Intramedullary Mature Cystic Teratoma in a Young Adult: A Rare Tumor - Aayush Shrestha; Binod Bijukachhe; Javed Ahmad Khan; Ram Krishna Dahal; Sandip Kumar Yadav (Case Reports in Orthopedics)
Intradural mature teratomas are spinal tumors containing all the germinal layers and rarely present in adulthood. This study describes an unusual case of intradural mature teratoma in a 19-year-old male who presented with persistent lower limb pain and difficulty in micturition. The magnetic resonance imaging (MRI) scan showed heterogeneously enhancing intramedullary mass in the L3-L4 vertebral region and was associated with tethering of the spinal cord. Scalloping of the posterior aspect of vertebral body and narrowing of the pedicles were present. Subtotal excision of the tumor was done because of its adherence to the conus. Attempt to completely excise such adherent intramedullary tumors can lead to permanent neurological deficits. The tissue was sent for histopathological examination which showed tissue from all the three germinal layers confirming the diagnosis. The patient showed improvement of symptoms following the surgery. This study also compared the literature of similar cases and the treatments available for this disease.